Banks’ non-revenue exposures: analytical framework for identification, determinants and management strategies - Pavković, Anita (Oeconomica Jadertina, 2022)
The banks as specialists in underwriting and risk management are mostly exposed to credit risk in their operations and non-revenue exposures are to the greatest extent the result of approved risky loans. The aim of the paper is to determine the key elements from the definition of bad placements and their evolution, factors of representation, trend and structure, and provide recommendations to bank managers in selecting the strategies to manage the credit portfolios of poor quality for general optimization of the bank’s own business efficiency. Knowledge and experiential synthesis of various approaches in primary and secondary research of recent decades have been used to create the content of the paper. Key determinants of non- revenue exposure of banks were identified through an innovative analytical framework and analysis of current market data and proposed solutions. It was successfully achieved through comparison and critical experiential evaluation, starting from the aspect of modernizing the business models of banks in today’s reformed and post-crisis regulatory, supervisory and business framework of bank operations. Hence, the paper is a specific meta-analysis of previous research results obtained through a systematic inception point and a foundation for new scientific research papers in the Croatian language.